Tunnelling-induced landslides: Trigging mechanism, field observations and mitigation measures. (August 2022) - Zhu, Binbin; Lei, Mingfeng; Gong, Chenjie; Zhao, Chenyang; Zhang, Yunliang; Huang, Juan; Jia, Chaojun; Shi, Chenghua
Highlights: The instability mechanism of the landslide is clarified. Anchor cable reinforcement is applied to prevent slope failure. Double side-wall heading method is used for portal excavation under collapse condition. Research results show that the treatment methods worked effectively. Lessons learned from this incident have been presented. Abstract: This paper reports a collapse accident of slope instability at the entrance of Taizhen Tunnel in Qujiang Section of Hangxinjing Expressway in China. The landslide instability mechanism was studied by field observation and testing. Considering the stability of the landslide and the disturbance effect of secondary tunneling construction, comprehensive reinforcement measures were proposed. The monitoring data showed that good results were achieved. In addition, the effectiveness analysis of the treatment scheme was further examined via numerical simulation. The analysis results show that slope reinforcement before tunnel excavation can not only prevent slope failure but also reduce the deformation of the supporting structure. The improved double side-wall heading method has less disturbance to the slope and is more conducive to the overall stability of the slope. Finally, the lessons learned were summarized, providing insights for preventing future similar incidents from reoccurring.